Analisis Faktor Kesulitan Belajar Siswa pada Materi Pecahan Pembelajaran Matematika Kelas 5 SDN Dupak 1 - Andika Adinanda Siswoyo; M. Fadlillah; Ida Fitriyani; Cahya Wilda Syahningrum (Lembaga Yasin AlSys, 2025)
Elementary school students often encounter difficulties in learning fraction concepts, particularly in understanding the ideas and computational procedures related to mixed fractions. This study aims to identify the factors influencing mathematics learning difficulties in the topic of fractions among fifth-grade students at SDN Dupak 1 Surabaya. A descriptive qualitative approach was employed, involving thirty students and one classroom teacher as research subjects. Data were collected through semi-structured interviews, learning outcome tests, and documentation. The data analysis followed the Miles and Huberman model, encompassing data collection, data reduction, data display, and conclusion drawing. The results indicate that 73.3% of students scored below the Minimum Mastery Criterion (Kriteria Ketuntasan Minimal, KKM) of 70. These difficulties are attributed to external factors such as monotonous teaching methods, an unsupportive learning environment, and limited engaging instructional media. Additionally, internal factors such as low learning motivation and weak foundational understanding of fraction concepts were found to be major contributors. The study concludes that innovative teaching strategies, the provision of engaging learning resources, and a supportive learning environment are essential for improving students’ understanding of fractions. These findings offer theoretical contributions to the study of mathematics learning difficulties at the elementary level and provide practical implications for teachers and educational institutions in designing more effective interventions.